From Worms to Drug Candidate: The Story of Odilorhabdins, a New Class of Antimicrobial Agents - Racine, Emilie; Gualtieri, Maxime (Frontiers in Microbiology, 2019)
A major issue currently facing medicine is antibiotic resistance. No new class of antibiotics for the treatment of Gram-negative infections has been introduced in more than 40 years. We screened a collection of Xenorhabdus and Photorhabdus strains in the quest to discover new structures that are active against the most problematic multidrug-resistant bacteria. These species are symbiotic bacteria of entomopathogenic nematodes and their life cycle, the richness of the bacteria’s genome in non-ribosomal peptide synthetase (NRPS) and polyketide synthase (PKS) genes, and their propensity to produce secondary metabolites with a large diversity of chemical structures make them a good starting point to begin an ambitious drug discovery program. Odilorhabdins (ODLs), a novel antibacterial class, were identified from this campaign. These compounds inhibit bacterial translation by binding to the small ribosomal subunit at a site not exploited by current antibiotics. Following the development of the total synthesis of this family of peptides, a medicinal chemistry program was started to optimize their pharmacological properties. NOSO-502, the first ODL preclinical candidate was selected. This compound is currently under preclinical development for the treatment of multidrug-resistant Gram-negative infections in hospitalized patients.